Claim Extension of Time and Prolongation Cost Management Using The Last Planner System Method - Dwi Aji Wicaksono; Ferry Hermawan; Sukamta Sukamta (Eduvest - Journal of Universal Studies, 2025)
This study addresses the challenges faced by service providers in construction projects, particularly in dealing with changes in work that may affect the project’s timeline and cost. Changes can introduce risks of loss, especially when claims for extension of time (EOT) and additional costs incurred due to prolongation are not properly approved by the Employer. Failure to submit a valid claim for EOT and prolongation costs can result in substantial financial losses for the service provider. The research aims to develop a method for effectively managing these risks by integrating the output of the Last Planner System (LPS) into the administrative support data for claims. This method is used to calculate delay events and create a structured, reliable claim evidence document. The findings suggest that using the LPS framework can help construction managers systematically document and justify delays and cost impacts, thereby improving the likelihood of claim approval. This approach can enhance the efficiency of claims management and reduce financial risks for service providers. The study’s implications highlight the importance of proactive planning and proper documentation in managing construction project risks, emphasizing the need for robust administrative systems to support claims for delays and associated costs.